Application Of Geometry In Planning And Building Design In Modern Architecture - Firdi Agniyal Qolbi; Nadira Zahra Humaira; Najma Syamsia Fasya; Wahyunengsih (Universitas Negeri Semarang, 2025)
This study explores the application of geometry in building planning and design in modern architecture. In applying geometry in building planning, researchers examine public opinion on the role of geometric elements in increasing architectural value. This study uses a descriptive quantitative method by distributing questionnaires to collect data from 39 respondents. Geometric shapes in building design have become the basis of architectural design, and this study explores the application of geometry in building planning and design in modern architecture. In applying geometry in building planning, researchers examine public opinion on the role of geometric elements in increasing architectural value. This study uses a descriptive quantitative method by distributing questionnaires to collect data from 39 respondents. Geometric shapes in building design have become the basis of architectural design, creating a building with aesthetic and functional value. These findings reveal that geometric design is essential in creating harmony, efficiency, and visual appeal of modern buildings. To strengthen the data from the questionnaire, the researcher also used a qualitative method using an online interview instrument with three people with an architectural background. Respondents agreed that applying geometric concepts contributes to architectural structures' distinct identity and modernity. To strengthen the data from the questionnaire, the researcher also used a qualitative method using an online interview instrument with three people with an architectural background. Furthermore, respondents agreed that applying geometric concepts contributes to the distinct identity and modernity of architectural structures. This study highlights the critical role of geometry in bridging technical design with artistic expression in contemporary architecture.